Droga ku zjednoczeniu. PPR i PPS w powiecie bialskim w latach 1947-1948 - Tarkowski, Paweł (Komunizm: System - Ludzie - Dokumentacja, 2015)
The years 1947-1948 were the period of intensive actions, which aim was to unify the Polish Workers' Party (Polish: Polska Partia Robotnicza, PPR) with the Polish Socialist Party (Polish: Polska Partia Socjalistyczna, PPS) and which the coping stone was the Unification Congress that was held from December 15th to December 21st, 1948. At this meeting the commonorganisation emerged under the name the Polish United Workers' Party (Polish: Polska Zjednoczona Partia Robotnicza, PZPR). The whole operation was carried out under a communist diktat, who took actions to weaken PPS through elimination of the internal opposition, implementation of submissive people to the management of the party, and absorption by PPR. The purpose of this article is to present the organization state ofPPR and PPS in the period between 1947 and 1948, the interparty cooperation and the establishment of county structures of PZPR.